FAMILIE – Scalable Community Assistance with Ethical AI in Smart Cities - Laakkonen, Mika; Pietiläinen, Ville; Kaivo-oja, Jari; Vanhanen, Minna; Huttunen, Hanna-Leena (Italy, 2026)
Abstract – The FAMILIE project leverages advanced AI to address the fragmentation and lack of digitalization in-home services by developing a scalable, community-based platform for families in smart cities. Through pilots in Oulu and Rovaniemi, the project will commercialize a mobile application and a community economy-based operating logic powered by AI. This approach ensures that AI-driven service needs are met locally, reducing unnecessary logistics and environmental impact. The AI-enabled platform's foundation can be scaled and implemented in other urban areas in Finland and abroad, promoting sustainable development and equitable distribution of profits within the service ecosystem.
Electronic media & the visual arts : EVA 2025 Florence : 26 May 2025